Reducing Binge Drinking in Adolescents through Implementation of the Strategic Prevention Framework. Issue 1 (March 2016) - Anderson‐Carpenter, Kaston D.; Watson‐Thompson, Jomella; Chaney, Lisa; Jones, Marvia
Abstract: The Strategic Prevention Framework (SPF) is a conceptual model that supports coalition‐driven efforts to address underage drinking and related consequences. Although the SPF has been promoted by the U.S. Substance Abuse and Mental Health Services Administration's Center for Substance Abuse Prevention and implemented in multiple U.S. states and territories, there is limited research on the SPF's effectiveness on improving targeted outcomes and associated influencing factors. The present quasi‐experimental study examines the effects of SPF implementation on binge drinking and enforcement of existing underage drinking laws as an influencing factor. The intervention group encompassed 11 school districts that were implementing the SPF with local prevention coalitions across eight Kansas communities. The comparison group consisted of 14 school districts that were matched based on demographic variables. The intervention districts collectively facilitated 137 community‐level changes, including new or modified programs, policies, and practices. SPF implementation supported significant improvements in binge drinking and enforcement outcomes over time ( p < .001), although there were no significant differences in improvements between the intervention and matched comparison groups ( p > .05). Overall, the findings provide a basis for guiding future research and community‐based prevention practice in implementing and evaluating the SPF.